Evaluation of soil fertility status of a lowland (Humic Gley) soil to rice crop. - Paula, Miralda Bueno de; Carvalho, Janice Guedes de; Soares, Antônio A.; Nogueira, Francisco Dias (Pesquisa Agropecuaria Brasileira, 2014)
In order to find out nutrient deficiencies and their relative importance for plant growth, a greenhouse experiment was conducted using rice plants growing in pots with a Humic Gley soil, at the water saturation level, using the missing element technique. The treatments were: control (no fertilizer added); complete fertilizer treatment (N, P, K, Ca, Mg, B, Cu, Fe, Mn and Zn) and complete minus one nutrient each of the time. It was verified a marked reduction in dry matter production in absence of N and P. The omission of K, Cu, Zn also reduced the dry matter yields but such reductions were not significantly. It seems that the omission of Ca and Mg reduced root dry matter yield. The data indicate that soil organic matter levels was not related to N availability in this soil. They also indicated that critical levels adopted were not adequate to measure the available P, Cu and Zn in this soil to rice plants.